Toxicity test of desorbed chromium from polluted soil around tannery industry in Yogyakarta-Indonesia by using Brassica juncea and Helianthus annuus L. - Suherman Suherman; Wina Akmarina; Wulandari Sutiawan; Nurul Hidayat Aprilita; Mudasir Mudasir; Kinichi Morita (Universitas Jenderal Soedirman, 2019)
Indonesia’s target to be a new industrial country makes a wide chance in the developing of many industrial sectors. The main problem is the disruption of environmental balance due to poorly managed liquid waste released by the industry. Heavy metal such as chromium (Cr) is the typical pollutant generated from tannery industry in Indonesia. Toxicity test of desorbed chromium ions from polluted soil around tannery industry in Yogyakarta-Indonesia by using Brassica junceaand Helianthus annuus L.has been carried out. In this research, soil samples were dividedinto four sample points based on the distances from the waste water point sources. Metal content and some physico-chemical properties including ash content, total organic carbon, and cation exchange capacity were determined in this study. Furthermore, the chromium ions adsorption and desorption from polluted soils were investigated and measured by atomic adsorption spectrophotometry (AAS). Thus, ecotoxicity testsof soil eluates from desorption experiments wereperformed with Brassica junceaand Helianthus annuus L.The resultsshowed that sample III had the highestCr content at916mgkg–1.The adsorption isotherm of Cr ions into soils followed Langmuir isotherm with the highest maximum adsorption capacity value at 14.286 mg kg-1in the sample point IV (unpolluted soil). The optimum desorption of chromium occurred at pH 3. Toxicity test showed that Cr ions had toxic effect to Brassica junceaand Helianthus annuus L.